Peningkatan Efisiensi dan Daya Saing Perbankan Syari’ah - Inni Basyarah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2016)
The concept of efficiency is a fundamental concept and born of economic concepts. Nonetheless, the concept of efficiency can be defined from various viewpoints and backgrounds. In general, the efficiency can be directed to a concept about achieving an outcome with optimal use of resources. The level of cost efficiency of Islamic banking is obtained by performing a comparison between the posts earnings assets (earning assets) or the output of banking to the total amount of costs incurred. By doing this comparison will be obtained efficiency index, which is where the greater value of this ratio, indicating higher levels of efficiencies gained by a bank